Influence of Cutting Intervals and Transition Periods on Chemical Composition Variability of Selected Tropical Grasses under Flooded Savanna Conditions of Arauca, Colombian Orinoquia. (2023)
The floodplain savannah is a tropical ecosystem that sustains grazing livestock, mainly by its grass’s diversity, of which scarce knowledge regarding the chemical composition and influencing factors. The aim was to evaluate the chemical composition variability of some native and introduced grasses grown in different physiographic positions of the floodplain savannah at transition periods and different cutting intervals. Five grasses from the “bank” (native species: Paspalum plicatulum, Axonopus compressus, Panicum versicolor, and Paspalum sp.; introduced species: Mulato I) and four from the “low” (native species: Leersia hexandra, Acroceras zizanioides, and Hymenachne amplexicaulis; introduced species: Urochloa humidicola) were sampled at 30, 40, and 50 cutting interval days during the “dry–rainy” and “rainy–dry” transition periods. The cuts were made with a 1 m2 frame to estimate forage biomass. The chemical compositions were analyzed by near-infrared spectroscopy. The influences of the cutting intervals and transition periods on chemical composition variables were evaluated through principal component analysis (PCA). Grass chemical variability was explained by eleven variables, including a digestible fraction, namely crude protein (CP), ash, ether extract (EE), total digestible nutrients (TDN), dry matter digestibility (DMD), metabolic energy (ME), phosphorus (P), and sulfur (S); and a partial digestible or undigestible fraction, namely neutral detergent fiber (NDF), lignin, and hemicellulose (HC). Grasses from the “low” position or with 30 cutting interval days in the rainy–dry transition period presented the highest proportion of the digestible fraction. Introduced grasses showed reduced nutritional value from 40 days onwards, whereas the L. hexandra, H. amplexicaulis, A. zizanioides, and P. versicolor native grasses were the least affected by the studied cutting intervals and transition periods. These native grasses constitute an important sustainable food resource for livestock in the flooded savanna ecosystem.